Cybercrime Legislation in The Age Of Digital Transformation: Challenges and Future Directions - Naomi Sinclair; Jamar White (International Journal of Law, Crime and Justice, 2024)
This article explores the challenges of developing effective cybercrime legislation in the era of rapid digital transformation. By analyzing current laws across various jurisdictions, the study identifies gaps in legal frameworks that cybercriminals exploit, such as issues related to jurisdiction, anonymity, and cross-border crime. Findings indicate that, while several nations have made strides in strengthening cybercrime laws, a cohesive international approach and consistent policy updates are essential to keep pace with the evolving nature of cyber threats. The paper advocates for enhanced international collaboration, cross-border enforcement mechanisms, and adaptable legal frameworks that can respond to future digital transformations.